Ta có a2(b+c)+b2(c+a)+c2(a+b)=a3+b3+c3+3abc
Trừ 2 vế đi 6abc ta có: a2(b+c)+b2(c+a)+c2(a+b)+6abc=a3+b3+c3−3abc
⇔(ab2−2abc+ac2)+(a2b−2abc+bc2)+(a2c−2abc+b2c)=(a+b+c)(a2+b2+c2−ab−ac−bc)
⇔a(b−c)2+b(c−a)2+c(a−b)2=(a+b+c)12[(a−b)2+(b−c)2+(c−a)2]
⇔2a(b−c)2+2b(c−a)2+2c(a−b)2=(a+b+c)[(a−b)2+(b−c)2+(c−a)2]
⇔a(b−c)2+b(c−a)2+c(a−b)2=(a+b)(a−b)2+(a+c)(a−c)2+(b+c)(b−c)2
⇔(a−b)2(a+b−c)+(b−c)2(b+c−a)+(c−a)2(c+a−b)=0
Do a,b,c là 3 cạnh cả tam giác nên a+b−c>0 ; b+c−a>0 ; c+a−b>0
Mặt khác (a−b)2≥0 ; ......................9
Nên đẳng thức xảy ra khi (a−b)2=(b−c)2=(c−a)2=0⇔a=b=c⇒ Tam giác ABC đều